Nilai-nilai Kearifan Lokal dalam Kesenian Tari Bangilun di Kabupaten Temanggung - Elana Rachmawati; Tutik Wijayanti; Sunarto; Agustinus Sugeng Priyanto (Universitas Negeri Semarang, 2026)
Globalization has had a considerable impact on the shift of culture in Indonesia. The existence of cultural changes in society has made the arts shift towards commercialism. However, this does not mean that all traditional arts have disappeared. Bangilun dance is a traditional art that is able to adapt until now. The objectives of this research are as follows: 1) How is the history of the emergence of Bangilun Dance?; 2) What are the local wisdom values behind Bangilun Dance?; 3) How is the existence of Bangilun Dance performances in the community? This research was conducted using a qualitative method. The location of this research is Kledung Village, Kledung District, Temanggung Regency. The results of the research in this thesis show that Bangilun Dance is a dance that has long appeared and was lost and then revived in Kledung Village and continues to experience renewal. The values of local wisdom contained in Bangilun Dance, among others: religious value, historical value, nasinalism value, mutual cooperation value, independent value, moral value, and aesthetic value. The existence of Bangilun Dance is still well maintained with the support of the community and government.